Synthesis, Characterization and Antibacterial Studies of Some Transition Metal Complexes with the Schiff Base of a Heterocyclic Aldehyde - Kothari, Richa; Sharma, Brajraj (Asian Journal of Chemistry, 2011)
Metal complexes of Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) with a new Schiff base derived from 2-acetylpyrrole and o-phenylenediamine are reported. The complexes have been characterized using chemical analysis, spectroscopic methods (IR, UV-VIS, 1H NMR), conductometric and magnetic data. According to these data, an octahedral geometry for metal (II) complexes are proposed. Antibacterial activity of the ligand and its metal complexes were studied against to Staphylococcus aureus, Bacillus subtilis, Salmonella typhi and E. coli.